COMPARATIVE EVALUATION OF OOCYTE RECOVERY METHODS IN GOATS - R.L. Dar; S. Kumar; G.R. Bhat (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The present study was aimed to assess the oocyte retrieval methods in goats using multifactorial approach (retrieval techniques, season, presence or absence of corpus luteum. The mean number of good and total oocytes recovered per ovary were significantly higher (p<0.05) for slicing method (2.94 ± 0.06, 6.46 ± 0.03) compared to puncture (1.23 ± 0.04, 4.12 ± 0.14) and aspiration (0.74 ± 0.06, 2.94 ± 0.13) techniques. The number of good and fair quality oocytes were also significantly higher during winter season than summer season. Furthermore ovaries without corpus luteum produced significantly higher (p<0.05) number of good quality oocytes compared to ovaries with corpus luteum. (5.78±0.11 vs 3.24±0.08). In conclusion, good quality oocytes could be recovered by slicing technique from ovaries without CL collected during winter season.